2000
DOI: 10.1038/sj.cgt.0235
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide-mediated tumor cell killing of cisplatin-based interferon-γ gene therapy in murine ovarian carcinoma

Abstract: We have determined the role of nitric oxide (NO)-mediated tumor cell killing in the treatment of an animal model of murine ovarian carcinoma grown in the peritoneum with a combination of cisplatin and cationic liposomes containing an expression vector for interferon-␥ (IFN-␥). The approach was to determine whether the therapy was effective in mice homozygous for a disrupted inducible NO synthase (iNOS) allele; these mice were unable to produce NO in response to IFN-␥. iNOS (Ϫ/Ϫ) mice treated with both cisplati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In nephrotoxicity, the increase in NOx production after IFO administration could be a secondary event following the increase in inducible nitric oxide synthase [39, 40]. Our study showed similar correlation in which the increase in NOx production accompanied with iNOS increase expression level after IFO administration.…”
Section: Discussionsupporting
confidence: 77%
“…In nephrotoxicity, the increase in NOx production after IFO administration could be a secondary event following the increase in inducible nitric oxide synthase [39, 40]. Our study showed similar correlation in which the increase in NOx production accompanied with iNOS increase expression level after IFO administration.…”
Section: Discussionsupporting
confidence: 77%
“…Tumor-bearing mice sequentially receiving cisplatin and a liposomal interferonc gene completely killed murine ovarian tumor cells or inhibited tumor growth with long-term survival (Son 1997a). The effectiveness of this combination therapy is largely due to sensitization of tumor cells by cisplatin for the subsequent lipofection (Son and Huang 1994).…”
mentioning
confidence: 99%
“…It also acts as a preservative of liver GSH content and prevents LPO. This effect may be due to its antioxidant activity [80][81][82].…”
Section: Discussionmentioning
confidence: 99%